Faraway, so close: Perceptions of the metaverse on the edge of madness - Cruz, M.; Oliveira, A.; Pinheiro, A. (Computers, 2024)
With the evolution of technologies, virtual reality allows us to dive into cyberspace through different devices and have immersive experiences in different contexts, which,, we call virtual worlds or multiverse (integrating Metaverse versions). Through virtual reality, it is possible to create infinite simulated environments to immerse ourselves in. Future internet may be slightly different from what we use today. Virtual immersion situations are common (particularly in gaming), and the Metaverse has become a lived and almost real experience claiming its presence in our daily lives. To investigate possible perspectives or concepts regarding the Metaverse, virtual reality, and immersion, we considered a main research question: To what extent can a film centered on the multiverse be associated with adults’ Metaverse perceptions? Considering that all participants are adults, the objectives of this study are: (1) Verify the representations of the Metaverse; (2) Verify the representations of immersion; (3) Verify the representations of the multiverse; (4) Verify the importance of a film (related to the Metaverse and the multiverse) on the representations found. This study—framed in a Ph.D. research project—analyzed the participants’ answers through an online survey using two films to gather thoughts, ideas, emotions, sentiments, and reactions according to our research objectives. Some limitations were considered, such as the number of participants, the number of questionnaire questions and the knowledge or lack of the main concepts. Our results showed that a virtual world created by a movie might stimulate the perception of almost living in that supposed reality, accepting the multiverse and Metaverse not as distant concepts but as close experiences, even in an unconscious form. This finding is also a positive contribution to a discussion in progress aiming for an essential understanding of the Metaverse as a complex concept.